Urgensi Program Studi Ilmu Hadis pada Perguruan Tinggi Islam terhadap Penyebaran Hadis Palsu pada Era Digital dalam Tinjauan Maqashid Syariah - Abdul Rahman Ramadhan, Abdul Rahman Ramadhan; Siti Aisyah Nur Sari, Siti Aisyah Nur Sari (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
This study examines the urgency of the Hadith Science Department at Islamic Universities in Indonesia in the Digital Era in the Review of Maqashid Syariah. The development of the digital era has had a positive impact on the development of hadith science, such as the emergence of various applications and electronic books that support learning and the ease of getting information. However, the ease of social media has resulted in the spread of weak and even fake hadiths in society that affect the practice of worship of the Muslims without being based on hadith that can be practiced. As an implementation of the maintenance of religion (hifdzu al-din), it is important for Islamic universities in Indonesia to have a Hadith Science Departement in order to produce graduates who are competent in the field of Hadith Science to spread the correct understanding of the takhrij hadith that is spread in the community. This can only be done by missionaries with backgrounds as students who have a critical attitude and are competent in preaching on social media. This research is library research, with content analysis and deductive analysis approach as data analysis technique. The purpose of this research is to provide an overview of the important role and urgency of the existence of the Department of Hadith Science in fighting the spread of fake hadiths in the digital era. The results of this research showed that there were only 38 Hadith Science Departement from 99 State Islamic Universities and only 2 of them received